Implementasi Artificial Intelligence (AI) di Obrit Future Academy - Rezeky Nur Amalia; Agus Salim; Agus Hadi Utama (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The government is obliged to provide the best educational services for the younger generation in order to create superior quality human resources as regulated by Law of the Republic of Indonesia Number 20 of 2003 concerning National Higher Education. The Ministry of Education, Culture, Research and Technology established the Independent Campus Orbit Future Academy (OFA) program which is an institution that is a pioneer in developing adaptive and innovative learning models. There are two main dimensions carried out by OFA to commit to improving the quality of life, namely providing special skills learning and the application of Artificial Intelligence (AI). Skills development at OFA aims to solve complex problems in the context of retail inventory management. Therefore, this study will discuss further the implementation of AI in retail inventory management with computer vision carried out at OFA. This research includes descriptive qualitative research with data collection techniques in the form of observation and research carried out directly at Orbit Future Academy. Data were analyzed using library research techniques. The findings show that the application and modeling of AI systems can be applied in retail inventory management through Python programming. The existence of AI can be applied in developing applications that have a real impact on the business sector and solving retail investment problems. Specifically, Computer Vision was developed as a smart and efficient solution for managing inventory. The resulting technology is a system that can see and recognize products automatically from visual images, minimize slow stock updates, optimize operational efficiency and reduce human error. Thus, overall the application of AI through Computer Vision in OFA can be an innovative solution developed as the latest technology to improve retail inventory.